Technical Feasibility of Enterotomy Closure with Knotless Barbed Suture Material (V-Loc 180) in Esophagojejunostomy Using Linear Stapler during Totally Laparoscopic Total Gastrectomy for Gastric Cancer - Dong Jin Kim; Wook Kim; Jun Hyun Lee (Journal of Investigative Surgery, 2017)
Purpose: Intra-corporeal esophagojejunostomy (EJ) using a linear stapler creates a stapler entry hole that requires secure closure during the totally laparoscopic total gastrectomy (TLTG) procedure for gastric cancer. Since a standard method has not been established yet, the feasibility of using V-loc 180 (Covidien, Mansfield, MA, USA) suture material was evaluated in this study. Materials and methods: During January 2012 to March 2015, 25 patients who underwent linear stapling EJ and V-loc 180 closure of remaining enterotomy were included in this study. Basic clinico-pathological characteristics, surgical outcomes, and short-term complications were analyzed. Results: The mean patient age was 60.4 ± 8.5 years. Nineteen males and six females were included in this study. The mean body mass index was 25.3 ± 2.3 kg/m2. There were 22 stage-I, 2 stage-II, and 1 stage-III gastric cancer patients. The mean operation time was 240.5 ± 44.6 min, and the time for anastomosis was 38.8 ± 11.2 min. The procedures were successfully performed in all cases without any intra-operative complications. There was one case of EJ leakage that occurred at the corner of EJ staple line and not at the enterotomy closure site. Conclusions: The closure of the remaining enterotomy site using V-loc 180 suture following linear stapler EJ is technically feasible and safe during the TLTG procedure. However, further experience and results from other surgeons are necessary to generalize this procedure.